Learning Beyond Literacy Through Radio Vis A Vis From Demonetisation To E-Monetisation (Trinity Journal of Management, IT & Media (TJMITM), 2017)
Radio has played and is playing an important role in public  awareness and mass communication. Marconi's invention  revolutionised the whole Western World in the last century but in  India its impact was reflected very late. Earlier programmes on  radio were themed on infotainment, i.e. a combination of  information and entertainment. But in post-independence era a  third factor of education too became an integral part of broadcast.  An exhaustive cum descriptive study has been carried out to find  out the impact of the programmes done by AIR on  demonetisation of Rs.500 and Rs. 1000 currency notes. Impact  of demonetisation on Indian society has been studied by co relating it's with my earlier study, expanding from 2003 to 2016.  The results are interesting and even support some pre established facts of wave's communication. These days, it is  becoming a common notion that Radio may not survive in long  run and it may even become obsolete in near future. Feedbacks  given by the listeners through various means have broken the  notion of decreasing popularity of wave's communication. But the  impacts of some programmes like 'Mann Ki Baat' of our Prime  Minister Sh. Narender Modi and recently mounted series of  programmes on Demonetisation further break this myth. During  the gestation period of Demonetisation five programmes were  done on National Hook up in the form of live Phone-in Programmes, four National programmes under National  Programmes of Talks, eight programmes on FM Rainbow  Networks and on an average one or two programmes were  broadcast daily on local networks. Besides this Prime Minister  Shri Narendera Modi raised the issues twice in his popular series,  “Mann Ki Baat”. Radio series and programmes of mass appeal can undergo a  long way by having deep and sustaining effect on target  audience. By adopting different formats of programme  production, monotony of the listeners can be broken. During the  rising trend of new media the traditional wave media of Radio can  prove as a source of Government and Public participation for  continuous advancement of knowledge among the masses,  particularly in remote and rural areas, where the new media is yet  to gain its assess. This study shows that during any unforeseen  situation that may arise can be faced by learning process,
Keywords: Broadcast; Wave; Science Serials; Programmes; Listeners; Formats; Target; Audience; Mann Ki Baat